Explaining the variable penetrance of CNVs: Parental intelligence modulates expression of intellectual impairment caused by the 22q11.2 deletion. Issue 6 (8th March 2016) - Klaassen, Petra; Duijff, Sasja; Swanenburg de Veye, Henriëtte; Beemer, Frits; Sinnema, Gerben; Breetvelt, Elemi; Schappin, Renske; Vorstman, Jacob
Abstract : The role of rare genetic variants, in particular copy number variants (CNVs), in the etiology of neurodevelopmental disorders is becoming increasingly clear. While the list of these disorder‐related CNVs continues to lengthen, it has also become clear that in nearly all genetic variants the proportion of carriers who express the associated phenotype is far from 100%. To understand this variable penetrance of CNVs it is important to realize that even the largest CNVs represent only a tiny fraction of the entire genome. Therefore, part of the mechanism underlying the variable penetrance of CNVs is likely the modulatory impact of the rest of the genome. In the present study we used the 22q11DS as a model to examine whether the observed penetrance of intellectual impairment—one of the main phenotypes associated with 22q11DS—is modulated by the intellectual level of their parents, for which we used the parents' highest level of education as a proxy. Our results, based on data observed in 171 children with 22q11DS in the age range of 5–15 years, showed a significant association between estimated parental cognitive level and intelligence in offspring (full scale, verbal and performance IQ), with the largest effect size for verbal IQ. These results suggest that possible mechanisms involved in the variable penetrance observed in CNVs include the impact of genetic background and/or environmental influences. © 2016 Wiley Periodicals, Inc.